Sovereign Wealth Funds and State Immunity - Argentini, Marco, (International Law E-Books Online, Collection 2025., 2024)
How does the hybrid nature of SWFs affect the application of state immunity to these funds? May an SWF be sued in foreign courts for wrongful acts committed in the course of its investment activities? Can SWF investments be attached by a private creditor seeking to enforce an investment arbitration award against the fund's state of nationality? This monograph addresses these questions from the perspective of the 2004 New York Convention and six selected jurisdictions (US, UK, France, Germany, Italy, China), with the broader aim of highlighting potential new standards for implementation of the state immunity rule to SWFs.